From Conflict to Common Ground: Why anti-trafficking can be compatible with challenging the systemic drivers of everyday abuses - Cockbain, Ella (Anti-Trafficking Review, 2020)
Response to the ATR debate proposition ‘It is worth undermining the anti-trafficking cause in order to more directly challenge the systems producing everyday abuses within the global economy.’